A Graphical Tool for Visualizing Bernoulli Stochastics - Zhai, Xiaomin; von Collani, Elart (International Journal of Emerging Technologies in Learning (iJET), 2009)
This paper continues the work of the article â??Strategies for Teaching a Novel Approach to Handling Uncertainty Scientifically via Internet